Debt, Boom, Bust: A Theory of Minsky-Veblen Cycles - Jakob Kapeller; Bernhard Schütz (Johannes Kepler University of Linz, Department of Economics, 2012)
This paper reflects on the development leading to the recent crisis and interprets this development as a series of events within a Minsky-Veblen Cycle. To illustrate this claim we introduce conspicuous consumption concerns, as described by Veblen, into a stock flow consistent Post Keynesian model and demonstrate that, under these conditions, a decrease in income equality leads to a corresponding increase in debt-financed consumption demand. Here Minskyian dynamics come into play: increased credit demand leads to a corresponding rise in credit supply, which, eventually, gives rise to a debt-financed consumption boom. As the solvency of households decreases and interest rates move up, banks reduce lending, triggering household bankruptcies and, finally, a recession. What follows is a stable period of consolidation, where past debts are repaid, financial stability is regained and conspicuous consumption motives may gradually take over again. We illustrate this approach to the current crisis and its explanatory validity by extending our stock-flow consistent model into a dynamic simulation.
Keywords: B52; D11; E12; E20; G01; 330